Effect of the PIVO Device on the Procedure of Phlebotomy from Peripheral IV Catheters. (22nd May 2018) - Adams, Suzanne; Toroni, Bridget; Lele, Meenal
Abstract : Short peripheral catheters (SPC) are an existing conduit into many patients' veins and line draws from SPC are a desired method of routine blood collection especially in difficult venous access patients. The PIVO device facilitates blood collection through SPC and is being used clinically in a number of hospitals. This study aimed to determine the appropriate wait time following a flush and the minimum waste volume required to obtain an undiluted blood sample when using the PIVO device and how that differed from current guidelines from SPC line draws. A clinical study was conducted examining the analyte results of samples drawn with PIVO through a SPC at varying wait times following a saline flush. Both an initial waste volume and a postwaste sample were compared to a venipuncture control. The resulting samples showed no saline dilution as measured by sodium and creatinine results at all studied wait times. These findings suggest that blood collections using the PIVO device can produce a clinically valid sample with a 30-second wait following a SPC flush and no waste volume prior to sample collection.